2018
DOI: 10.1212/wnl.0000000000005250
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment and intracranial atherosclerotic stenosis in general population

Abstract: Our results suggest that asymptomatic ICAS is independently associated with cognitive impairment and dementia in whites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 42 publications
2
27
0
Order By: Relevance
“…This was expected as it is consistent with previous studies 5,8) . Our observation further supports the use of the CAC score as a predictor of brain diseases, because ICAS is a significant cause of ischemic stroke 16) and has been shown to be associated with cognitive impairment/ dementia in a community-based study in the USA 25) .…”
Section: Advance Publication Journal Of Atherosclerosis and Thrombosissupporting
confidence: 82%
“…This was expected as it is consistent with previous studies 5,8) . Our observation further supports the use of the CAC score as a predictor of brain diseases, because ICAS is a significant cause of ischemic stroke 16) and has been shown to be associated with cognitive impairment/ dementia in a community-based study in the USA 25) .…”
Section: Advance Publication Journal Of Atherosclerosis and Thrombosissupporting
confidence: 82%
“…Furthermore, the results of the present study showed that chronic cerebral hypoperfusion selectively reduced the neuronal activity of the limbic system and impaired recognition memory. Chronic cerebral hypoperfusion is caused by small vessel disease 16 or atherosclerosis of multiple large vessels 11 and is known to be common in cognitively normal elderly and patients with cognitive impairment 17,18 . Thus, strategies to reduce the risk of cerebrovascular disease, including lifestyle modification, medication, rehabilitation, and surgery, can help to delay the progression of or even prevent AD dementia 5 .…”
Section: Discussionmentioning
confidence: 99%
“…1) Although all these findings were derived from Caucasians, ≥50% stenosis in the intracranial arteries is considered to lead to dementia and cognitive impairment, and affect higher brain function. 2) Many investigators have found that intracranial or extracranial arterial stenosis can affect cognitive function or mood disturbance. According to WASID evaluation, MMSE scores are significantly lower in patients with >70% than 40-70% ICA stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial internal carotid artery (ICA) stenosis, which is a relatively common occurrence among Asian populations including Japanese, sometimes causes cognitive decline in patients with or without evidence of ipsilateral ischemic lesions. [1][2][3][4][5][6][7] Although cognitive function after carotid artery endarterectomy (CEA) or carotid artery stenting (CAS) improves in patients with extracranial ICA stenosis, the effects of percutaneous transluminal angioplasty (PTA) for cognitive impairment in patients with intracranial ICA stenosis have not been determined 3,8,9) Here, we describe a patient who underwent neuroendovascular treatment for cognitive impairment during the acute phase.…”
Section: Introductionmentioning
confidence: 99%